Nitrate contamination in groundwater and its health implications in a semi-urban region of Titrol block, Jagatsinghpur district, Odisha, India - Das, Rashmirekha; Subba Rao, N.; Sahoo, H.K.; Sakram, G. (Physics and chemistry of the earth. Parts A/B/C, 2023)
Nitrate (NO3−) in drinking water poses serious health risks worldwide. Exposure to ionic sources of NO3− pollution in groundwater and health risks to children and adults require management measures to be taken prior to the development of urban activities. Groundwater samples were collected from a semi-urban region of Titrol block, Jagatsinghpur district, Odisha, and analysed for chemical variables. The content of NO3− ranged from 2 to 92 mg/L with an average of 34.26 mg/L, in which 83.33% of the groundwater samples contained NO3− above 10 mg/L. This is the starting point of water pollution activity in water. Computed values of the Nitrate Pollution Index (NPI) varied from −0.40 to 8.20 with an average of 2.42. According to NPI, 16.67%, 16.67%, 10%, 13.33%, and 43.33% of groundwater samples were unpolluted, slightly polluted, moderately polluted, significantly polluted, and very significantly polluted, covering 1.45%, 6.07%, 27.43%, 37.46%, and 27.59% of the study region, respectively. The correlation of NO3− with well depth and other chemical variables indicated significant degradation of groundwater quality by agricultural activities, leading to vulnerability of health conditions. According to Chronic Health Risk (CHR), CHR varied from 0.063 to 3.067 (1.067) for children and 0.042 to 1.917 (0.712) for adults, with 56.67% and 23.33% of groundwater samples above the acceptable level of 1.0. They covered 59.57% and 6.49% of the study region, respectively. Therefore, careful planning of prevention methods is necessary to reduce the health risk of NO3−.This study contributes to UNDP's Sustainable Development goals 2030 for a healthy environment. [Display omitted] •Agricultural input is a major source in groundwater pollution.•Nitrate Pollution Index in 83.33% of groundwater samples indicated different levels of pollution.•Chronic Health Risks were observed in 56.67% and 23.33% of groundwater samples for children and adults, respectively.•Nitrate vulnerability risk was found to be 1.50 times higher in children than in adults.